Entomological diversity associated with tomato cultivation under organic shelter in the El-Outaya Region, Biskra (Algeria) - Khalila BENGOUGA; Souad TAHAR CHAOUCHE; Farida BETTICHE; Reguia ZGUERROU; Haroun FADLAOUI (Studia Universitatis Babeș-Bolyai. Biologia)
The aim of the present work is to determine harmful and beneficial insects associated with tomato greenhouse cultivation in the arid region of El-Outaya (Biskra, Algeria). Insect trapping was conducted using yellow water plates and yellow glue traps. Faunistic data have revealed the presence of 2754 individuals distributed on seven orders, 33 families and 38 species of insects. From specific point of view, the majority of these insects were represented by potential insect pests with sixteen phytophagous species amongst them three species attacking tomatoes. Whereas nine species are predators and two pollinators. Our results can be used to plan strategies for the management of harmful pests and beneficial insects associated with the tomato greenhouse crops in this locality.